State-level and system-level opioid prescribing policies: The impact on provider practices and overdose deaths, a systematic review - Beaudoin, MD, MS, Francesca L.; Banerjee, MPH, Geetanjoli N.; Mello, MD, MPH, Michael J. (Journal of Opioid Management, 2016)
Objective: In response to persistent public health concerns regarding prescription opioids, many states and healthcare systems have implemented legislation and policies intended to regulate or guide opioid prescribing. The overall impact of these policies is still uncertain. The aim of this systematic review was to examine the existing evidence of provider-level and patient-level outcomes preimplementation and postimplementation of policies and legislation constructed to impact provider prescribing practices around opioid analgesics. Design: A systematic search of MEDLINE, EMBASE, the Web of Science, and the Cochrane Database of Systematic Reviews was conducted to identify studies evaluating the impact of opioid prescribing policies on provider-level and patient-level outcomes. The systematic review was conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Results: Eleven studies were included in the review. A meta-analysis was not possible due to between-study heterogeneity. Six of the studies assessed state-level policies, and five were at the level of the healthcare system or hospital. Studies showed temporal associations between policy implementation and reductions in opioid prescribing, as well as opioid-related overdoses. Results were mixed regarding the impact of policies on misuse. The majority of the studies were judged to be of low quality based on the GRADE criteria. Conclusions: There is low to moderate quality evidence suggesting that the presence of opioid prescribing policy will reduce the amount and strength of opioid prescribed. The presence of these policies may impact the number of overdoses, but there is no clear evidence to suggest that it reduces opioid misuse.